Surgical Management of Inguinal Hernia in Female Dogs - Kumar, Rajesh; Aakanksha; Tiwary, Ramesh; Singh, G. D.; Singh, M. K.; Kumar, Mithilesh; Anjana, Kumari; Archana (International Journal of Bio-resource and Stress Management, 2026)
The present study was conducted during January, 2025 to May, 2025 at the Surgery Outpatient Department, Teaching Veterinary Clinical Complex, Bihar Veterinary College, Patna, Bihar, India to describe the surgical management of acquired inguinal hernia in two adult female dogs. Both animals reported with a history of swelling in the inguinal region following mild trauma. Diagnosis was based on clinical examination, palpation, and ultrasonographic findings, which revealed the presence of omentum and a segment of intestine within the hernial sac. Surgical correction was performed under general anaesthesia induced with propofol and maintained with isoflurane. Following aseptic preparation, the female dog was placed in dorsal recumbency and the surgical area was properly draped. A skin incision was made over the inguinal swelling, extending slightly beyond the hernial ring. Blunt dissection was used to isolate the hernial sac from adjacent tissues. The herniated contents were then carefully reduced back into the abdominal cavity, and excess sac tissue was removed. The edges of the hernial ring were lightly freshened with a scalpel, and the defect was closed using 2-0 polydioxanone in a vest-over-pants suture pattern. Postoperative management included ceftriaxone–tazobactam, meloxicam, routine wound dressing, and the use of an Elizabethan collar. Both dogs showed smooth recovery without postoperative complications or recurrence during the follow-up period. The study concluded that early diagnosis and surgical management using the vest-over-pants technique provided an effective method for the successful management of inguinal hernia in dogs.